Overview of Marriage Customs and Bridal Make Up at Gadang House 21 Nagari Abai Sangir Room, South Solok Regency, West Sumatra - Wilya Santika; Hayatunnufus Hayatunnufus (Jurnal Tata Rias dan Kecantikan, 2022)
This study explores information about traditional wedding ceremonies and bridal makeup in Nagari Abai Sangir in terms of wedding ceremony processions, bridal makeup, bridal fashion and accessories and the meaning of bridal fashion and accessories. This study aims to describe the wedding ceremony procession, the form of bridal makeup, the form of bridal clothing and accessories, describe the meaning of bridal clothing and accessories. This type of research is qualitative research. This research instrument is the researcher himself and is assisted by supporting instruments such as stationery, tape recorders and cameras. Data collection techniques are carried out by means of observation, interviews and documentation. The techniques of checking the validity of data in this study are the extension of observations, increased persistence, triangulation and auditing. The steps to analyze data are data collection, data reduction, data presentation and making  conclusions. The results of this study are 1) marriage ceremonies at the gadang house 21 Nagari Abai Sangir rooms including ceremonies before marriage, wedding ceremonies and post-wedding ceremonies, 2) in Nagari Abai Sangir before the bride and groom are made up first carry out the ritual of eating betel while reciting prayers called pamanih, 3) the form of clothing and accessories of the bride in the gadang house 21 nagari Abai Sangir room consists of suntiang,  kuruang clothes, salendang, orok, kaluang omeh, galang furnace, tarompa tinggi, while the groom's clothes consist of shirts, sarawa rocking saruang cloth, litau bridal accessories, kaluang and keris, 4) suntiang contains the meaning of a bride must be able to carry a heavy burden after having a family, kuruang clothes show minangkabau democracy, salendang contains the meaning of there are parts of a woman's body that others should not know, orok contains the meaning of women must cover aurat, neck jewelry as beauty and wealth sipemakainya, hand jewelry has the meaning to act must have limits, high tarompa contains the meaning of travel must be careful,  while the meaning of the groom's dress includes Shirts symbolizing the greatness of the wearer and having a big spirit, sarawa goyang symbolizes all acts of work must have a size, saruang cloth symbolizes having to obey customs and sharak, litau symbolizes a leader in the family and his people, keris symbolizes a person must be careful and think first before acting, shoes symbolize a leader must manage to take his family in a more important direction  good. It is recommended that it be able to consider and preserve the customs of Marriage in Nagari Abai Sangir in terms of bridal makeup, bridal fashion and accessories and their meaning.